Comparison of Gelation Time and Polyalcohol Effect on Hydrogels from Domestic and Wild Silk Fibroins. (8th April 2012) - Zhao, Huijing; Xiong, Siyong; Li, Mingzhong; Zhang, Qiang; Liu, Guiyang
Abstract : Silk fibroin (SF) hydrogels were obtained from both domestic ( Bombyx mori ) and wild ( Antheraea pernyi ) silkworms from aqueous silk fibroin solutions at room temperature. The gelation time of the Antheraea pernyi ( A. pernyi ) SF solution was significantly shorter than that of the Bombyx mori ( B. mori ) SF solution. The secondary structures of the two kinds of hydrogels were also compared. In order to further reduce the gelation time, various amounts of polyethylene glycol (PEG) were blended with the silk fibroins of A. pernyi and B. mori . The gelation time of both A. pernyi SF and B. mori SF decreased with the increased amount of PEG. After freeze-drying, the hydrogels were characterized through X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and Raman spectroscopy. Results showed that the addition of polyalcohol did not change the main secondary structure of the hydrogels. However, the addition of polyalcohol did reduce the gelation time and triggered additional formation of β -sheets.